Limited Liability and the Trade-off between Risk and Incentives - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
everal empirical findings have challenged the traditional trade-off between risk and incentives. By combining risk aversion and limited liability in a standard principal-agent model the empirical puzzle on the positive relationship between risk and incentives can be explained.
Keywords: D01; M5; D82; J3; 330; limited liability; piece rates; risk aversion; risk-incentives trade-off; Risiko; Ökonomischer Anreiz; Agency Theory; Risikoaversion; Beschränkte Haftung; Theorie